Laminin-521 promotes quiescence in isolated stellate cells from rat liver - Rohn, Friederike; Benk, Amelie Saskia; Geiger, Fania; Spatz, Joachim P. (Biomaterials, 2018)
The laminin α5 protein chain is an element of basement membranes and important to maintain stem cells. Hepatic stellate cells (HSC) are liver-resident mesenchymal stem cells, which reside in a quiescent state on a basement membrane-like structure in the space of Dissé. In the present study, laminin α5 chain was detected in the space of Dissé of normal rat liver. Since HSC are critical for liver regeneration and can contribute to fibrosis in chronic liver diseases, the effect of laminins on HSC maintenance was investigated. Therefore, isolated rat HSC were seeded on uncoated polystyrene (PS) or PS coated with either laminin-521 (PS/LN-521) or laminin-211 (PS/LN-211). PS/LN-521 improved HSC adhesion and better preserved their retinoid stores as well as quiescence- and stem cell-associated phenotype, whereas HSC on PS/LN-211 or PS developed into myofibroblasts-like cells. To improve the homogeneity as well as the presentation of laminin molecules on the culture surface to HSC, laminin-functionalized, gold-nanostructured glass surfaces were generated. This approach further enhanced the expression of quiescence-associated genes in HSC. In conclusion, the results indicate that LN-521 supports the quiescent state of HSC and laminin α5 can be regarded as an important element of their niche in the space of Dissé.
Gesehen am 09.04.2019